2016
DOI: 10.1561/107.00000025
|View full text |Cite
|
Sign up to set email alerts
|

"Is This Food Healthy?": The Contextual Influence of Prior Foods on Healthiness Perceptions

Abstract: Perceptions of a food's healthiness are a critical input to consumers' decision making about what to eat, and therefore understanding factors that influence these healthiness perceptions are important. We examine the role of prior exposure to other foods in impacting healthiness perceptions. We propose and find that the healthiness of foods previously encountered can influence healthiness perceptions and consumption intentions for ambiguously healthy snacks, and importantly, this influence differs based on one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although we observed a carryover effect on goldfish crackers after participants encounter a relatively healthy product in an elongated container, the carryover effect may be different when facing other products. That is, although we used goldfish because their health perceptions were considered sufficiently malleable (Davis et al, 2016), given a pretest found them to be relatively healthier than cookies and relatively less healthy than carrots, a different effect may materialize on other products. For example, a negative carryover effect of elongation may be observed on products thought to be relatively unhealthier than goldfish (but relatively healthier than chocolate chip cookies).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we observed a carryover effect on goldfish crackers after participants encounter a relatively healthy product in an elongated container, the carryover effect may be different when facing other products. That is, although we used goldfish because their health perceptions were considered sufficiently malleable (Davis et al, 2016), given a pretest found them to be relatively healthier than cookies and relatively less healthy than carrots, a different effect may materialize on other products. For example, a negative carryover effect of elongation may be observed on products thought to be relatively unhealthier than goldfish (but relatively healthier than chocolate chip cookies).…”
Section: Discussionmentioning
confidence: 99%
“…As such, after participants viewed the advertisement, but before answering questions about the healthiness and volume of the product contained inside the glass, participants were asked to rate the perceived healthiness of three snack products on a 9-point scale (1 = "very unhealthy" to 9 = "very healthy"). These snacks consisted of a known healthy snack (carrots), a known unhealthy snack (cookies), and the focal product of interest: an ambiguously healthy/unhealthy snack (goldfish crackers) that was used in past research (Davis, Haws, & Redden, 2016). We expected that carrots and cookies would be rated closer to the end poles of the healthiness scale, restricting their ability to be manipulated; therefore, the health ratings of the goldfish crackers would serve as our primary measure of whether elongation cues participants to think about healthiness in subsequent, unrelated evaluations.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…Future research may also examine sequential choices, such as decisions within the context of the entire dining experience, to determine whether the impact of decision strategy on dessert choices remains the same given the healthy or unhealthy choices made during the same consumption episode, such as appetizers and entrées that precede the dessert choice. Research shows that the healthiness of foods encountered previously can influence judgments of the healthiness of other foods (Davis et al, 2016); thus the foods chosen earlier in the meal may impact perceptions of the dessert options. Additionally, a longitudinal study examining how decision strategies may influence long-term consumer health could build on the present examination of rejection strategy as a viable intervention to reduce guilt associated with unhealthy choices.…”
Section: Discussionmentioning
confidence: 99%